2009
DOI: 10.1111/j.1445-2197.2009.04865.x
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of minimum clinically important differences in surgical trials

Abstract: Background:  The minimum clinically important difference (MCID) is the smallest difference in outcome between the groups that would be of clinical interest. It influences the estimates that are made to determine the required sample side. The aim of this study was to explore the reporting of the MCID in surgical trials. Method:  Surgical trials that were published between January 1981 and December 2006 in five prestigious surgical journals were evaluated. Selected for study were trials that studied two groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…First, MCID helps to estimate the required sample size so that a study has sufficient power to detect the true differences and therefore assess treatments better. (17,18) It is encouraging that there is an increase in the number of surgical trials including sample size estimates in the manuscripts over the last 3 decades; however, a study conducted by Kashani et al revealed that only 21% of the surgical trials considered MCID in their sample size calculations. (17) For to be adequately powered and not report negative results, appropriate MCID values should be considered in the sample size estimation at the beginning of trials.…”
Section: Discussionmentioning
confidence: 99%
“…First, MCID helps to estimate the required sample size so that a study has sufficient power to detect the true differences and therefore assess treatments better. (17,18) It is encouraging that there is an increase in the number of surgical trials including sample size estimates in the manuscripts over the last 3 decades; however, a study conducted by Kashani et al revealed that only 21% of the surgical trials considered MCID in their sample size calculations. (17) For to be adequately powered and not report negative results, appropriate MCID values should be considered in the sample size estimation at the beginning of trials.…”
Section: Discussionmentioning
confidence: 99%
“…As has been noted, ‘a numerical score of a function or symptom is sometimes difficult to interpret and it gives the clinician little information as to the actual severity of symptoms being experienced by the patient’. The area in which a quantitative understanding of PROs is needed most is comparative effectiveness research, where studies may often be underpowered to detect the changes they wish to detect, in part because of inconsistent use and reporting of PRO measures.…”
Section: Discussionmentioning
confidence: 99%
“…Kashani et al 5 . found that only 21% (100/486) of admissible surgical trials mentioned a value for the minimum clinically important difference when estimating the sample size.…”
Section: The Minimum Important Differencementioning
confidence: 99%